Biologics in dermatology: An integrated review - Virendra N Sehgal; Deepika Pandhi; Ananta Khurana (Wolters Kluwer Medknow Publications, 2014)
The advent of biologics in dermatologic treatment armentarium has added refreshing dimensions, for it is a major breakthrough. Several agents are now available for use. It is therefore imperative to succinctly comprehend their pharmacokinetics for their apt use. A concerted endeavor has been made to delve on this subject. The major groups of biologics have been covered and include: Drugs acting against TNF-α, Alefacept, Ustekinumab, Rituximab, IVIG and Omalizumab. The relevant pharmacokinetic characteristics have been detailed. Their respective label (approved) and off-label (unapproved) indications have been defined, highlighting their dosage protocol, availability and mode of administration. The evidence level of each indication has also been discussed to apprise the clinician of their current and prospective uses. Individual anti-TNF drugs are not identical in their actions and often one is superior to the other in a particular disease. Hence, the section on anti-TNF agents mentions the literature on each drug separately, and not as a group. The limitations for their use have also been clearly brought out.